An Analysis of Students’ Challenges in Speaking English in the Tenth Grade of Madrasah Aliyah Al-Hariri Tebo - Yulita, Lili Rahma; Alfian; Nisaul Fadillah (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This research aims to comprehend the challenges that Madrasah Aliyah Al-Hariri Tebo's tenth-grade students encountered when speaking English, as well as the solutions that the teachers offered to address these issues. The researcher used a descriptive qualitative approach. The research subjects for this study were seven students from class X at Madrasah Aliyah Al-Hariri Tebo and two English teachers. The researcher's needed criteria for seven students with the lowest test scores during English lessons were used to select the seventh student. Through observation and interviews, the data was acquired. Based on the study's findings, the researcher discovered that students at Madrasah Aliyah Al-Hariri Tebo at the tenth grade had the following five challenges when speaking English: challenges in pronunciation, challenges in vocabulary, challenges in grammar, challenges in fluency, and challenges in comprehension. Then, there are five solutions for teachers to overcome these challenges, namely: Use group or pair work, based on the activity’s easy language, provide some dialogue or instruction in effective communication, keep students speaking the target language, and the last solution is to select a task and topic to pique attention carefully.